Electrochemical Oxidation and Electroanalysis of Organic Pollutants on Electrodes Modified with Metallophthalocyanines (Mpcs) - Ureta-Zanartu, M (Springer International Publishing, 2016)
Due to the importance of electroremediation of organic compounds, both in water decontamination processes and in previous steps to avoid contamination of water, in this chapter we review works in this area in which electrodes modified with metallophthalocyanines were used. Mostly electrodes based on Ni(II)-phthalocyanines have been studied, although in some cases cobalt phthalocyanines were used. The active species in the Ni(II)-based compounds is the Ni(III) which is formed at high enough potentials, and which chemically oxidizes the organic compound. This oxidation proceeds more easily on electrodes modified with metallophthalocyanines than on a Ni(OH)2 electrode, since in the first case the oxidation is facilitated by the hydrophobic environment generated by the phthalocyanine on the electrode surface. In the case of Co(II)-based N4 complexes, mainly used in electroreduction processes, the active species would be Co(I). The use of electrodes modified with metallophthalocyanines in electroanalysis is also discussed, as well as the possible improvement of non-electrochemical remediation processes by the addition of metallo-phthalocyanines. We think that the electrochemical remediation with suitable electrodes could reach a higher efficiency than chemical processes. © Springer International Publishing Switzerland 2016.